Dynamics of ozone and nitrogen oxides at Summit, Greenland. II. Simulating snowpack chemistry during a spring high ozone event with a 1-D process-scale model. (September 2015) - Murray, Keenan A.; Kramer, Louisa J.; Doskey, Paul V.; Ganzeveld, Laurens; Seok, Brian; Van Dam, Brie; Helmig, Detlev
Abstract: Observed depth profiles of nitric oxide (NO), nitrogen dioxide (NO2 ), and ozone (O3 ) in snowpack interstitial air at Summit, Greenland were best replicated by a 1-D process-scale model, which included (1) geometrical representation of snow grains as spheres, (2) aqueous-phase chemistry confined to a quasi-liquid layer (QLL) on the surface of snow grains, and (3) initialization of the species concentrations in the QLL through equilibrium partitioning with mixing ratios in snowpack interstitial air. A comprehensive suite of measurements in and above snowpack during a high O3 event facilitated analysis of the relationship between the chemistry of snowpack and the overlying atmosphere. The model successfully reproduced 2 maxima (i.e., a peak near the surface of the snowpack at solar noon and a larger peak occurring in the evening that extended down from 0.5 to 2 m) in the diurnal profile of NO2 within snowpack interstitial air. The maximum production rate of NO2 by photolysis of nitrate (NO3 − ) was approximately 10 8  molec cm −3  s −1, which explained daily observations of maxima in NO2 mixing ratios near solar noon. Mixing ratios of NO2 in snowpack interstitial air were greatest in the deepest layers of the snowpack at night and were attributed to thermal decomposition of peroxynitric acid, which produced up to 10 6 molec NO2  cm −3  s −1 . Highest levels of NO in snowpack interstitial air were confined to upper layers of the snowpack and observed profiles were consistent with photolysis of NO2 . Production of nitrogen oxides (NOx ) from NO3 − photolysis was estimated to be two orders of magnitude larger than NO production and supports the hypothesis that NO3 − photolysis is the primary source of NOx within sunlit snowpack in the Arctic. Aqueous-phase oxidation of formic acid by O3 resulted in a maximum consumption rate of ∼10 6 –10 7  molec cm −3  s −1 and was the primary removal mechanism for O3 . Highlights: A 1-D process-scale model accurately simulated variations in diurnal profiles of NOx . Diurnal profile maxima of NO2 at solar noon were attributed to NO3 − photolysis. Diurnal profile maxima of NO2 during the evening were attributed to HO2 NO2 decomposition. The primary removal mechanism for O3 was aqueous-phase oxidation of formic acid.